ENSURING MACROECONOMIC STABILITY THROUGH THE IMPLEMENTATION OF GREEN TRANSFORMATION - S.M. Kholkhojayev (Innovation Science and Technology, 2025)
In the world, as in many other factors, ensuring macroeconomic stability in the national economic system is a priority area for sustainable development of the green economy. The implementation of this process is also important for the national economy of Uzbekistan, and although much practical work has been done in this direction, there remain a number of problems that require scientific research in this area. This article focuses on these issues